(untitled) (The Pakistan Development Review, 2012)
Water is the most important constituent of life without which, life cannot exist. Water is a natural resource which is also used as an input for producing different goods in factories for industrial use, productivity of crops for agriculture use also used in our daily life for domestic purpose. Despite such an importance, still the World is experiencing the issue of water scarcity [WCD (2000)]. The supply of water does not meet its demand [Bengali (2009)]. Pakistan is an agrarian economy which is also heavily dependent on water. About 45 percent of the total employment is generated from Agriculture sector [Pakistan (2011)]. Main sources of water are rivers and rainfall. Balochistan is the largest province of Pakistan. Land size is 44 percent of the total land of Pakistan [Balochistan (2010)]. Land is fertile and provides conducive environment for Agriculture. Agriculture productivity is high in Balochistan. Many vegetables and crops are grown which results in many farmers and labours livelihood. It has got varieties of species of many fruits, particularly Apple. Important fruit crops grown are Apple, Grapes, Cherry and Peach. Climate is also suitable for crops growth particularly the deciduous fruits like apple, which requires low temperature during summer season. As far as quality is concerned, apple produced in Balochistan, especially at high altitude (1600 meters to 2000 meters) are superior in quality than that produced in the rest of the country. The main reason is that due to dryness of the climate in apple producing areas like Ziarat, Killa Abdullah, Pishin, Quetta etc. Apple is one of the most popular fruit. It is delicious and crunchy and is mostly liked by health conscious and fitness lovers as it is filled with rich phyto-nutrients, which is very essential for optimal health. It also contains antioxidants, which promotes health as well as prevents several diseases. Thus, apple truly justifies the famous sayings, “An apple a day keeps the doctor away.” One of the distinguishing features is that there are no fungal diseases and disease free apple can be stored for a longer period in cold storage. Also the abundance of sunshine in the growing season improves the colour of apple which fetches a good price in the domestic and foreign market.